Predictive PI controller for wireless control system with variable network delay and disturbance - Hassan, S.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
As control using wireless technology is receiving increased attention, its often associated with network delays and uncertainties. The use of PIDs proved inadequate to handle these challenges while model based controllers are complex. As a compromise, this paper examines the use of Predictive PI (PPI) controller in a wireless networked control environment characterized by both network delay and process deadtime. As against deadtime compensators, the PPI allows for model mismatch while still maintaining the simplicity of PIDs in terms of tunable parameters. Comparison of the simulation results for the thermal chamber while considering input disturbance and measurement noise showed that the PPI controller produce improved performance in terms of systems overshoot, rise time and integral absolute error in all cases. The PPI is still better than the other two controllers in terms of settling time for most cases. © 2016 IEEE.